The silent patient: a consideration of Gendlin's recommendations in the treatment of a silent adolescent - Le Roux, Jakob Daniel (Rhodes University, Faculty of Humanities, Department of Psychology, 1990)
This study comprises a dialogue between Gendlin's recommendations on the treatment of the silent patient and case-material taken from 39 sessions of psychodynamic psychotherapy with a 16 year old adolescent. The most characteristic feature of the therapy with this young person, was her pattern of silence and unresponsiveness. The aim of this study is to ascertain the usefulness of Gendlin's recommendations in the therapy of this category of patient. The dialogue between the suggested recommendations and the case- material served to illustrate the point that Gendlin's recommendations are of great value in the treatment of the silent adolescent. The value of these recommendations lie in their ability to comment meaningfully on the process of therapy with the silent patient by providing not only skills and techniques, but also a conceptual framework within which to contextualize the therapy. The recommendations were also found to be sensitive to some of the key issues of relevance to adolescence as a developmental phase. The case-study method was deemed an appropriate structure within which to conduct this examination.
Keywords: Gendlin, Eugene T, 1926-2017; Nonverbal people; Psychodynamic psychotherapy; Adolescent psychotherapy